A system to use electromagnetic tracking for the quality assurance of brachytherapy catheter digitization. Issue 10 (19th September 2014) - Damato, Antonio L.; Viswanathan, Akila N.; Don, Sarah M.; Hansen, Jorgen L.; Cormack, Robert A.
Abstract : Purpose: : To investigate the use of a system using electromagnetic tracking (EMT), post‐processing and an error‐detection algorithm for detecting errors and resolving uncertainties in high‐dose‐rate brachytherapy catheter digitization for treatment planning. Methods: : EMT was used to localize 15 catheters inserted into a phantom using a stepwise acquisition technique. Five distinct acquisition experiments were performed. Noise associated with the acquisition was calculated. The dwell location configuration was extracted from the EMT data. A CT scan of the phantom was performed, and five distinct catheter digitization sessions were performed. No a priori registration of the CT scan coordinate system with the EMT coordinate system was performed. CT‐based digitization was automatically extracted from the brachytherapy plan DICOM files (CT), and rigid registration was performed between EMT and CT dwell positions. EMT registration error was characterized in terms of the mean and maximum distance between corresponding EMT and CT dwell positions per catheter. An algorithm for error detection and identification was presented. Three types of errors were systematically simulated: swap of two catheter numbers, partial swap of catheter number identification for parts of the catheters (mix), and catheter‐tip shift. Error‐detection sensitivity (number of simulated scenarios correctly identified as containing an error/number of simulated scenarios containing an error) and specificity (number of scenarios correctly identified as not containing errors/number of correct scenarios) were calculated. Catheter identification sensitivity (number of catheters correctly identified as erroneous across all scenarios/number of erroneous catheters across all scenarios) and specificity (number of catheters correctly identified as correct across all scenarios/number of correct catheters across all scenarios) were calculated. The mean detected and identified shift was calculated. Results: : The maximum noise ±1 standard deviation associated with the EMT acquisitions was 1.0 ± 0.1 mm, and the mean noise was 0.6 ± 0.1 mm. Registration of all the EMT and CT dwell positions was associated with a mean catheter error of 0.6 ± 0.2 mm, a maximum catheter error of 0.9 ± 0.4 mm, a mean dwell error of 1.0 ± 0.3 mm, and a maximum dwell error of 1.3 ± 0.7 mm. Error detection and catheter identification sensitivity and specificity of 100% were observed for swap, mix and shift (≥2.6 mm for error detection; ≥2.7 mm for catheter identification) errors. A mean detected shift of 1.8 ± 0.4 mm and a mean identified shift of 1.9 ± 0.4 mm were observed. Conclusions: : Registration of the EMT dwell positions to the CT dwell positions was possible with a residual mean error per catheter of 0.6 ± 0.2 mm and a maximum error for any dwell of 1.3 ± 0.7 mm. These low residual registration errors show that quality assurance of the general characteristics of the catheters and of possible errors affecting one specific dwell position is possible. The sensitivity and specificity of the catheter digitization verification algorithm was 100% for swap and mix errors and for shifts ≥2.6 mm. On average, shifts ≥1.8 mm were detected, and shifts ≥1.9 mm were detected and identified.